Emerging trends and focus of giant cell tumor of bone research from 2001–2021: A visualization research - Han, Ying-Song; Yang, Yi-Fan; Chen, Gang; Yu, Hai-Liang; Zhang, Zhi-Guo; Zhou, Bin (Frontiers in Oncology, 2022)
Giant cell tumor of bone is a highly invasive benign tumor with a high postoperative recurrence rate. Objective: This study aims to analyze the research hotspots and trends of global research on giant cell tumor of bone in the past 20 years, to provide a reference for relevant personnel in this field to carry out academic research. Methods: The literature related to giant cell tumor of bone from 2001 to 2021 was retrieved from the Web of Science. The bibliometrics research method and VOS Viewer were used to extract and analyze the keywords of the journal authors’ research institutions, and the research status and development direction in the recent 20 years were visualized. Results: A total of 2063 articles were included. The number of global publications is increasing every year. The United States contributes the most to global research, with the most citations and the highest H-index. The journal Clinical Orthopaedics and Related Research published the most articles on this issue. “Denosumab” and “h3f3a” will get more attention and be the next popular hotspot in the future. Conclusion: The study of giant cell tumor of bone is a hot spot of continuous development and has an important contribution to human health.